2020
DOI: 10.2196/17167
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of a Web App for Cognitive Training (MeMo) Regarding Cognitive and Behavioral Performance in People With Neurocognitive Disorders: Randomized Controlled Trial

Abstract: Background Cognitive and behavioral symptoms are the clinical hallmarks of neurocognitive disorders. Cognitive training may be offered to reduce the risks of cognitive decline and dementia and to reduce behavioral symptoms, such as apathy. Information and communication technology approaches, including serious games, can be useful in improving the playful aspect of computerized cognitive training and providing motivating solutions in elderly patients. Objective … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
71
0
7

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 54 publications
(94 citation statements)
references
References 41 publications
1
71
0
7
Order By: Relevance
“…Calabrò et al 96 showed a significant improvement in the attention process and executive functioning among older participants. In Robert et al, 93 there were indications of steady results in cognitive performance, suggesting less or slowed deterioration. Park et al 92 showed improvements in memory, but otherwise, no differences compared to the control group who used a conventional computer‐based training program.…”
Section: Resultsmentioning
confidence: 94%
See 2 more Smart Citations
“…Calabrò et al 96 showed a significant improvement in the attention process and executive functioning among older participants. In Robert et al, 93 there were indications of steady results in cognitive performance, suggesting less or slowed deterioration. Park et al 92 showed improvements in memory, but otherwise, no differences compared to the control group who used a conventional computer‐based training program.…”
Section: Resultsmentioning
confidence: 94%
“…87 4.7 | Training and maintenance of cognitive ability 9% (n = 8) of included studies described interventions aiming to improve or preserve cognitive skills and functions and reduce depressive symptoms among older people. [89][90][91][92][93][94][95][96] The interventions used mobile, web-based or virtual reality gaming software, [89][90][91][92]95 wearable and monitoring sensors, 94 a web-based app, 93 and an exercise robot. 96 The system in Lazarou et al 94 also included a caregiver interface for sharing information.…”
Section: Education To Support Self-efficacy and Social Inclusionmentioning
confidence: 99%
See 1 more Smart Citation
“…"MeMo" is a Web-based app for memory, attention, and mental flexibility training. In a randomized controlled trial, its effects on cognitive and behavioral symptoms were explored in 46 patients with neurocognitive disorders (32 participants were diagnosed with probable Alzheimer's disease and 14 with mixed disorders) [47]. In detail, the study compared patients using and not using "MeMo" for 12 weeks (four sessions per week).…”
Section: Cognitive Functionsmentioning
confidence: 99%
“…However, these limitations are not unique to this paper, as can be seen in recent game-related literature. For example, existing literature reporting studies with sample size of 46 [ 61 ], 20-minute game exposure time [ 62 ], or subjects recruited from a single institution [ 61 , 63 ] still provide novel and useful insights. Second, the fact that the actual food choices were made immediately after playing the game limits our observed effect to be the immediate effect.…”
Section: Discussionmentioning
confidence: 99%